Inhibition deficit in the spatial tendency of the response in multiple-domain amnestic mild cognitive impairment. An event-related potential study - Cespón, Jesús (Front Aging Neurosci, 2015)
Longitudinal studies have shown that a high percentage of people with amnestic mild cognitive impairment (MCI) develop Alzheimer’s disease (AD). Prodromal AD is known to involve deficits in executive control processes. In the present study, we examined such deficits by recording EEG in 13 single-domain amnestic MCI (sdaMCI), 12 multiple-domain amnestic MCI (mdaMCI) and 18 healthy elderly (control group, CG) participants while they performed a Simon task. The Simon task demands deployment of executive processes because participants have to respond to non-spatial features of a lateralized stimulus and inhibit the more automatic spatial tendency of the response. We specifically focused on the negativity central contralateral (N2cc), an event-related potential (ERP) component related to brain activity that prevents the cross-talk between direction of spatial attention and manual response preparation. The reaction time (RT) was not significantly different among the three groups of participants. The percentage of errors (PE) was higher in mdaMCI than in CG and sdaMCI participants. In addition, N2cc latency was delayed in mdaMCI (i.e., delayed implementation of mechanisms for controlling the spatial tendency of the response). The N2cc latency clearly distinguished among mdaMCI and CG/sdaMCI participants (area under curve: 0.91). Longer N2cc was therefore associated with executive control deficits, which suggests that N2cc latency is a correlate of mdaMCI.